Validity of a modified Demirjian system based on an Australian dataset – simple maturity score in age estimation. Issue 5 (2nd September 2016) - Chiam, Sher-Lin; Blenkin, Matthew; Taylor, Jane; Te Moananui, Raymond
Abstract : This pilot study is a validation of a modified Demirjian's System developed for the Australian population by Blenkin and Evans. The study sample comprised orthopantomographs of 230 individuals aged 2.5 to 14.5 years. Seven right mandibular teeth (excluding the wisdom tooth) were assessed and graded according to the Demirjian's stages of tooth development. Corresponding modified numeric scores for the stages were summed to form a simple maturity score from which age estimates were derived. The mean difference between the estimated and chronological age for girls was 0.02 years, 95% CI [-0.13, 0.17]. Paired-sample t-test results found this difference not to be statistically significant p = 0.81, <0.05. For boys, the method underestimated the age with a mean difference of –0.24 years 95% CI [–0.4, –0.08]. Paired t-test found this to be significantly different ( p = 0.003). This study found that the modified Demirjian's System of Blenkin and Evans is valid for use in the Australian population.